Additive Manufacturing of Cellulosic Materials with Robust Mechanics and Antimicrobial Functionality. Issue 4 (30th January 2017) - Pattinson, Sebastian W.; Hart, A. John
Abstract : Additive manufacturing of pure cellulosic objects is demonstrated via extrusion of cellulose acetate and conversion to cellulose, rendering parts with isotropic strength and high toughness. Ease of functionalization is shown by addition of antimicrobial dye to the printing ink, which kills 95% of bacteria upon exposure to light.